2015
DOI: 10.1038/nphys3557
|View full text |Cite
|
Sign up to set email alerts
|

Random focusing of tsunami waves

Abstract: Branched flow is a universal phenomenon of random focusing that occurs in wave or particle flows that propagate in weakly scattering, correlated random media. The consecutive effect of small random forces leads to regions of strong focusing which have the appearance of branches and originate from the formation of random caustics. This phenomenon has been experimentally and theoretically studied in various systems, ranging from experimental observations in electronic microdevices on the micrometer scale to theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Non-stationarities are also seen when wave packets travel through disordered systems. Even if the disorder is static, the correlations between the wave intensities measured at different positions versus time will change, when the direction or the composition of the wave packet is altered [3][4][5]. Finance provides another important example for this type of non-stationarity.…”
Section: Introductionmentioning
confidence: 99%
“…Non-stationarities are also seen when wave packets travel through disordered systems. Even if the disorder is static, the correlations between the wave intensities measured at different positions versus time will change, when the direction or the composition of the wave packet is altered [3][4][5]. Finance provides another important example for this type of non-stationarity.…”
Section: Introductionmentioning
confidence: 99%
“…Probably the most sensational manifestation are giant ocean freak waves of more than 20 m height, which have been confirmed to exist by measurements for the first time only little more than 20 years ago [1]. Heavy tailed intensity distributions and thus rogue waves, however, can be found in a variety of different contexts including optics [1] and microwave transmissions [2,3], as well as the propagation of sound [4] and tsunami waves [5].…”
Section: Introductionmentioning
confidence: 93%
“…Breathers have been extensively studied both theoretically and experimentally in optics and water waves [12][13][14][15][16][17]. Likewise have branched flows been studied in a variety of systems ranging from transport of electrons in the two-dimensional electron gas scattered by the disorder potential of impurities [18][19][20], via the scattering of wind driven ocean waves by ocean currents [21,22] to the focusing of tsunamis by small variations of the ocean floor topography [5]. Not only do branched flows in general lead to heavy-tailed intensity distributions [10,23], but experiments on microwave transmissions through disordered arrays of scatterers have shown that in combination with fluctuating sources they can lead to breather-like isolated rogue events [2].…”
Section: Introductionmentioning
confidence: 99%
“…In hydrodynamics, when the height of a wave is larger by a factor of 3 than average, this wave is considered extreme. For example, regarding the wave height of tsunamis, maxima several times higher than the average wave height have been reported [6]. In optics, however, fluctuations of much higher amplitudes compared to the average are often observed [25].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme events are ubiquitous in complex systems [1][2][3][4][5][6] and a lot of efforts are nowadays focused on developing reliable analysis techniques for their detection and prediction [7][8][9][10][11][12][13]. In many scientific fields, if an extreme event occurs in an unexpected way, it often has disastrous consequences.…”
Section: Introductionmentioning
confidence: 99%